Role of Q-carbon in nucleation and formation of continuous diamond film. (May 2021) - Narayan, J.; Bhaumik, A.; Gupta, S.; Joshi, P.; Riley, P.; Narayan, R.J.
Abstract: Formation of continuous and adherent diamond films on practical substrates presents a formidable challenge due to lack of diamond nucleation sites needed for diamond growth. This problem has been solved through the formation of interfacial Q-carbon layers by nanosecond laser melting of carbon layers in a highly undercooled state and subsequent quenching. The Q-carbon layer provides ready nucleation sites for epitaxial films on planar matching substrates such as sapphire, and polycrystalline films on amorphous substrates such as glass. Each laser pulse converts about a one-cm-square area, which can be repeated with a 100–200 Hz laser to produce potentially 100–200 cm 2 s -1 of diamond films. This is essentially a low-temperature processing, where substrate stays close to ambient temperature, because the total heat input is quite small. The Q-carbon layer is also responsible for improved adhesion of diamond films on sapphire and glass substrates. It is also argued that the formation of Q-carbon layer is also responsible for efficient diamond nucleation during negatively biased MPCVD diamond depositions. Graphical abstract: Image 1